Estudo multibanda do conteúdo estelar de regiões HII do Hemisfério Sul - Pinheiro, Márcio do Carmo (2012)
We present a multi-wavelength study of the stellar content of 11 optical/infrared Southern Galactic Hii regions with 10 h < α(J2000) < −17 h and −65° < δ(J2000) < −35°. Nine optical objects with no published or uncertain distances were examined in order to identify their ionising sources and to determine their distances, whereas young stellar objects (YSOs) and main sequence ionising stars were photometrically classified in the two infrared clusters. We carried out optical spectroscopy and UBV photometry of the stellar content of these Hii regions and obtained the distance of individual stars by spectroscopic parallax. To avoid using a fixed value for the total-to-selective extinction ratio RV , the reddening AV was determined directly by the colour-difference method. We classified as types O or B 24 out of the 31 stars for which optical spectra were obtained. In particular, we identified two new O stars in RCW98 and RCW99. The values for reddening obtained correspond to a mean hRV i = 3.44, which is about 10% higher of the mean value found for field stars over all directions of the Galaxy. For the Hii regions NGC3503, NGC6334, RCW55, RCW87, RCW98 e RCW99, we obtained more precise distances calculated as the median of the spectroscopic parallaxes obtained for two to six different stars in each nebulae, with an internal dispersion of less than 5%. Among the objects more obscured in the Norma region, we analysed the stellar content of the East part of the large complex of Hii regions GAL331.5-00.1, which contains eight bright extended radio sources. This study comprises the infrared clusters [DBS2003] 156 and [DBS2003] 157, respectively associated to Hii regions GAL331.11-00.51 and GAL331.31-00.34. In order to isolate the brightest 2MASS sources of their unresolved companions, we carried out JHK photometry with resolution better than 2MASS data. 47 Near-infrared (NIR) sources with Ks-band excess were identified following usual methods. Other 70 YSOs were also identified by using Mid-IR on-line data of the GLIMPSE survey. The search for radial-velocity measurements in the literature and the similarity between the stellar population explored have indicated the two regions as physically associated. With the determination of the spectroscopic parallaxes of four O-type and two B-type stars spread over the both clusters, this hypothesis was verified. The parallaxes of these 6 stars returned very compatible distances (hdhelioci = 3.30 ± 0.29 kpc). The Near- and Mid-IR counterparts of the IRAS source 16085-5138 was found close to the field of [DBS2003] 157. This source has showed typical colours of a Ultra-compact ii region (UCHii) and spectral index α = 3.6 between 2 and 25 μm, which is typical of YSOs immersed in protostellar envelopes. A lower limit to the bolometric luminosity of the protostar embedded was computed as L = 7.7×103L⊙ (M = 10M⊙), which corresponds to a BO-B1 zero-age star. The cluster [DBS2003] 157 was found to be spread over all ∼4′ × 4′ region demarcated by a intense shell-like dust emission, where a secondary massive star formation is going on, likely as a result of the interaction between this dust and stellar winds.